An English Placement Test at Three Different Periods: The Implementation and the Test Administrators’ Views - Basori, Basori; Mubarok, Harir; Rohmana, Wahyu Indah Mala; Bisriyah, Maslihatul; Jayanti, Septia Dwi; Maharany, Elva Riezky (Journal of English Teaching and Learning Issues, 2023)
This paper aims to explore the practice of an English placement test at one of the English education programs during three different testing periods (before the COVID-19 pandemic, during the pandemic, and after the pandemic). Further, the study sought to investigate the views of the test administrators, mainly focusing on the challenges they faced administering the test during the period mentioned. Using a qualitative case study approach, the researchers gathered the data from the results of observations and final reflections of the test administrators. The findings revealed that the placement test in three different periods applied similar three consecutive stages: the pre-testing stage, the testing day, and the post-testing stage. The goal of the test is also similar to that it is used to gauge the newly intake students entering TBIP. Rather than grouping students for specific classes, the placement test was conducted as a part of need analysis strategies to understand students’ English proficiency levels. While the placement tests before and after the pandemic have similarities, especially in preparation activities, the test format, and the test delivery, the placement test during COVID-19 differs. Despite those issues, the placement test administrators believed the test brought additional benefits. In addition to gauging the newly intake students’ English proficiency, the placement test was a way to start building positive relationships with students before meeting in an actual class. Hence, the test administrators have mixed feelings upon administering the placement test. Some final thoughts conclude the papers.